Implementation Of Remote Hand Tractor Control Device With The Use Of Solar Panels As Battery Charging - Hidayatullah, M Wahyu; Ariandi, Muhamad (Program Studi Teknik Elektro Universitas Khairun, 2024)
Technological progress has developed very rapidly along with the times. The hand tractor is a form of technological progress in agriculture. The use of hand tractors for processing agricultural land has replaced the function of buffalo in tillage activities because they are far superior in terms of effectiveness and efficiency. The hand tractor with a remote control system using flysky is the latest innovation created with the hope of increasing effectiveness and efficiency, as well as safety. and operator comfort in operating the hand tractor. With the application of solar panels as a charger for remote tractor control devices, this can save the use of electrical energy, this tool has proven successful in trials. Thus, this automated solution has the potential to increase productivity and efficiency in agriculture. System Performance When Using a Tractor. Through testing with 3 trials (6 hours, 7 hours, and 8 hours), the battery voltage remained above 12V. The combination of batteries and solar panels used ensures the system operates well during tractor use.